30 Key Questions that Unlock Management - BRIAN SUTTON, ROBINA CHATHAM (IT Governance Publishing, 2012)
Most people who find themselves in a management position for the first time are lost and ill-prepared. The challenge of stepping up to management is not something that can be overcome by attending a course or reading a book that abstractly talks about planning or motivation or delegation. There is a big difference between understanding the theory of how something works and being able to apply those ideas in practice. We work extensively with mid- and senior-level managers in all industry sectors and across national boundaries and cultures. We find the same issues whether we are working with IT folk, scientists, engineers, finance professionals, academics or sales people – they all ask us the same questions and they always start with the words ‘How do I …?’ But we have come to realise that generally, while they may have the book knowledge of what to do, they just have no idea of how to go about doing it. And we have also learned to listen to the subtext of the question. When people ask us: How do I delegate a task to my subordinate? they are not looking for an explanation of the process; they already know the process. What they are really asking is: How do I delegate to this person who used to be my friend but now works for me and I have realised is using our friendship to avoid things they don’t want to do? Similarly a plea of: I don’t understand my boss is often code for: How do I tell my boss I don’t know what they want me to do without looking stupid or incompetent?